Debridement, Antibiotics, and Implant Retention for Acute Periprosthetic Joint Infection - Zhang, Chao‐fan (Orthop Surg, 2020)
OBJECTIVE: To report on our clinical outcomes and on the experience of managing acute periprosthetic joint infection (PJI) with debridement, antibiotics, and implant retention (DAIR). METHODS: We performed a retrospective review of all patients who were diagnosed with acute PJI after primary hip or knee replacement surgeries and who were managed with DAIR in our prospective joint replacement registry from 2008 to 2019. The diagnosis of PJI was made according to the 2011 Musculoskeletal Infection Society (MSIS) criteria. The symptom onset duration, inflammatory marker levels (i.e. C‐reactive protein [CRP], erythrocyte sedimentation rate [ESR], white cell count [WBC], and synovial WBC count), functional scores including the Knee Society Score (KSS), the KSS functional score and the Harris Hip Score (HHS), bacteriology, and surgical outcomes of the patients were tracked and recorded. A paired sample of joint fluid and tissues was also sent for a metagenomic next‐generation sequencing (mNGS) test. A paired‐samples t‐test was used to compare the differences in the inflammatory markers and functional scores before and after surgery. RESULTS: A total of 24 patients with 7 infections after hip replacements and 17 infections after knee replacements were included. A total of 21 patients exhibited early postoperative infections, and 3 exhibited late acute hematogenous infections. During a mean follow‐up time of 29.2 ± 15.1 months, 22 patients were successfully treated, whereas 2 patients were unsuccessfully treated and required repeated DAIR. The overall success rate of DAIR was 91.7%. For staphylococcal infections, DAIR had a 100% success rate. Five patients who presented with symptoms between 4 and 8 weeks also achieved a 100% success rate. At the last follow‐up, the mean CRP level decreased from 52.6 ± 34.0 to 5.4 ± 3.5 (P < 0.001), and the mean ESR level decreased from 72.3 ± 34.3 to 20.2 ± 12.1 (P < 0.001). The mean KSS score increased from 44.8 ± 12.2 to 81.4 ± 9.2 (P < 0.001), and the mean KSS functional score increased from 38.1 ± 3.5 to 73.9 ± 23.0 (P < 0.001), and the mean HHS score increased from 34.4 ± 6.9 to 84.1 ± 15.1 (P < 0.001). The overall pathogen identification rate was 91.7% (22/24 cases). The success rates for Staphylococcus, Streptococcus, and the other pathogens were 100% (9/9 cases), 71.4% (5/7 cases), and 100% (6/6 cases), respectively. CONCLUSION: Debridement, antibiotics, and implant retention has a high success rate for the treatment of acute PJI and may be performed in selected patients whose symptoms have been sustained for over 4 weeks. A high rate of success for staphylococcal infections was reported with the use of DAIR.